Projects with the industry for the development of professional competences in industrial engineering and management - Lima, Rui M. (2014)
Training engineering students has been evolving towards the development of professional competences, both technical and transversal. These competences will enable new engineers to apply learning resources in professional contexts with greater efficacy. Thus, these engineers will be closer to the needs of industry. A learning methodology that has been used in these contexts is Project Based Learning (PBL). This paper presents a learning process based on PBL concepts, in which five teams of 5 to 7 students of Industrial Engineering and Management from the University of Minho, Portugal, developed projects in interaction with companies during a semester. This project is supported by 5 courses of the 7th semester: Organization of Production Systems, Information Systems for Production, Integrated Production Management, Ergonomic Study of Workplaces and Simulation. The objective of the students’ project is to make the analysis and present proposals for improvement of a part of the production system of a company. With the support of teachers, students should manage the interaction with an industrial company under the established partnership and present suggestions for improvements to their production system, considering contributions from the 5 courses of the semester. The aim of this paper is to describe the operational model of this PBL process, evaluate the results in terms of students’ learning and in terms of the perception of industry, and finally make proposals for improving the model. The evaluation of learning outcomes is based on the analysis of students’ project results, a questionnaire and a closing workshop of the project with students. The evaluation of the perception of industry partners is achieved using informal interviews with company representatives. The evaluation process shows that, from the participants’ perceptions, students have developed the competences that are expected and, in general, the teams are motivated by the outcome of their projects. They referred that there should exist better mechanisms of differentiation of individual classifications within the team. From the point of view of industry, the results are considered good, but there is a tendency to propose a greater focus on the objectives and results of the project. Considering these results, a change to the model is proposed, in order to increase the direction of the project. The proposal organizes the project into two very distinct phases: (1) analysis and diagnosis phase; (2) improvement phase. This change would explore the contents and competences expected of all courses during the analysis and diagnosis phase, and in second phase, the project would focus on developing specific solutions for the enterprise.